Дослідження Овруцької волості у північних р-нах Житомирської обл. у 2008 р. - Томашевський, А.П.; Павленко, С.В. (Археологічні дослідження в Україні, 2009)
The paper presents the results of field research in the northern regions of Zhytomyr Oblast by the Ovruch archaeological expedition of IA NASU. The works have been conducted within the program «Code of historic and cultural monuments» of Zhytomyr Oblast. The information about the most important monuments and their archaeological characteristics is published. The rescue excavations on the site of a national value near the village of Horodets in Ovruch Region are also described.